The Relational Approach and the Family - Rossi, Giovanna; Carrà, Elisabetta (Socialinė teorija, empirija, politika ir praktika, 2017)
The article is an illustration, from a sociological viewpoint, of the epistemological and methodological scope of the relational approach to the study of the family. From this perspective (Section 1), the family can be identified as a social relationship of full reciprocity between sexes 1 and generations, to be neither replaced nor confused with anything else (family genome), thus highlighting the advantages of the relational approach compared to other contemporary approaches, defined as relationist/relationistic. Section 2 focuses on the Added Value of the Relational Method from logical, methodological and empirical levels. The main traits of the family research are to consider the family as a unicum and its relational and historical nature. The AGIL scheme helps to analyse the family as a suigeneris relationship by identifying its constitutive resources (A), aims (G), norms (I) and latent cultural model (L).